A comparative study of lidocaine, botulinum toxin type a injection and dry needling in the treatment of myofascial pain syndrome - Kamanli, A; Kaya, A; Ozgocmen, S; Bayik, Y; Ardicoglu, O (B M J Publishing Group, 2003)
[Abstract Not Available]
Annual European Congress of Rheumatology -- JUN 18, 2003 -- LISBON, PORTUGAL